Naturalistic psilocybin use is associated with persisting improvements in mental health and wellbeing: results from a prospective, longitudinal survey - Nayak, Sandeep M.; Jackson, Hillary; Sepeda, Nathan D.; Mathai, David S.; So, Sara; Yaffe, Abigail; Zaki, Hadi; Brasher, Trey J.; Lowe, Matthew X.; Jolly, Del R. P.; Barrett, Frederick S.; Griffiths, Roland R.; et al. (Frontiers in Psychiatry, 2023)
The classic psychedelic psilocybin, found in some mushroom species, has received renewed interest in clinical research, showing potential mental health benefits in preliminary trials. Naturalistic use of psilocybin outside of research settings has increased in recent years, though data on the public health impact of such use remain limited.Methods: This prospective, longitudinal study comprised six sequential automated web-based surveys that collected data from adults planning to take psilocybin outside clinical research: at time of consent, 2 weeks before, the day before, 1-3 days after, 2-4 weeks after, and 2-3 months after psilocybin use. Results: A sample of 2,833 respondents completed all baseline assessments approximately 2 weeks before psilocybin use, 1,182 completed the 2-4 week post-use survey, and 657 completed the final follow-up survey 2-3 months after psilocybin use. Participants were primarily college-educated White men residing in the United States with a prior history of psychedelic use; mean age = 40 years. Participants primarily used dried psilocybin mushrooms (mean dose = 3.1 grams) for "self-exploration" purposes. Prospective longitudinal data collected before andafter a planned psilocybin experience on average showed persisting reductions in anxiety, depression, and alcohol misuse, increased cognitive flexibility, emotion regulation, spiritual wellbeing, and extraversion, and reduced neuroticism and burnout after psilocybin use. However, a minority of participants (11% at 2-4 weeks and 7% at 2-3 months) reported persisting negative effects after psilocybin use (e.g., mood fluctuations, depressive symptoms).Discussion: Results from this study, the largest prospective survey of naturalistic psilocybin use to date, support the potential for psilocybin to produce lasting improvements in mental health symptoms and general well-being.